Effects of copper and titania nanoparticles on MHD 3D rotational flow over an elongating sheet with convective thermal boundary condition. Issue 1 (31st December 2023) - Mishra, Swetapadma; Dalai, Renuprava; Swain, Kharabela
Abstract : Copper nanoparticles (NPs) are used as highly thermal conductive material as well as alloys. In the same way, titanium dioxide nanoparticles have wide usage in coating, waste water treatment, food industries and space crafts etc. The three dimensional (3D) rotational nanofluid flow and heat transfer over an elongating sheet with thermal radiation, heat source and thermal convective boundary condition is studied. The convective heat transfer currently discussed is the superposition of thermal conduction due to temperature gradient and heat energy transfer by the flowing fluid. This phenomenon has been combined with electrically conducting nanofluid subjected to magnetic field. Further, flow model includes rotation and translation which find applications in chemical and process industries. The boundary conditions on heat transfer involves Biot number ( Bi ) which is important because most of the problem reported in literature involves Nusselt number which is a relative measure of heat transfer coefficient and thermal conductivity, both related to flowing fluid. The solution involves Runge-Kutta forth order method with MATLAB code. It is found that for metallic nanofluid ( Cu ) temperature remains positive and for metallic oxide nanofluid ( TiO 2 ) the temperature remains negative, indicating thermal energy generation and absorption due to metal or metallic oxide as nanoparticles.